Implementasi Sistem Informasi Pelayanan Desa Kaliwungu Kabupaten Kudus - Solekhan Solekhan; Arief Susanto; Nafi Inayati Zahro; Budi Cahyo Wibowo (Universitas Muria Kudus, 2024)
Administrative processes have gradually shifted from manual methods to computerized ones in various public services for the community. The service team then made observations in Kaliwungu village and found that the need for computerized data and information processing was still very lacking. Therefore, the Service Team is trying to implement the system that has been implemented in Janggalan and in 11 villages in Mejobo sub-district. This system covers various aspects of data processing, including population data, family facilities and infrastructure, socio-economic conditions, access to education, and others. This system is expected to bridge the needs of village governments in managing data and information as well as in reporting to local governments. This system is expected to be able to support reporting to local governments by presenting and providing data recapitulation with appropriate indicators. Implementation of this system is carried out through training and mentoring methods for village government staff in Kaliwungu, which will then be passed on to the community.